2020
DOI: 10.31235/osf.io/3rmpt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pride and Protest: Emotional response in the aftermath of the Chilean social outburst

Abstract: In recent months, Chile, like many other countries around the world, has undergone a wave of widespread street protests calling for structural changes and challenging the “Chilean miracle.” This study uses an interrupted public opinion poll to assess the effect on the moral sentiments of the general population of the first weeks of the Chilean social crisis that began in October 2019. Our findings suggest that emotions toward the country, official symbols, and economic development were negatively affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…This effect is consistent with the accuracy-inducing hypothesis suggested by the institutional trust literature (Hakhverdian and Mayne 2012). In addition, recent studies have shown that the events of the Chilean Spring of October 2019 caused a stronger decline in national pride in this group than among other socio-economic sectors (Olivos, Ayala, and Leyton 2020). These events might have signaled certain structural problems that shift the support for the status quo and conservativism (Barozet and Espinoza 2016; Barozet and Fierro 2011), including the general positive attitudes toward the police that characterize this group (Dammert 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is consistent with the accuracy-inducing hypothesis suggested by the institutional trust literature (Hakhverdian and Mayne 2012). In addition, recent studies have shown that the events of the Chilean Spring of October 2019 caused a stronger decline in national pride in this group than among other socio-economic sectors (Olivos, Ayala, and Leyton 2020). These events might have signaled certain structural problems that shift the support for the status quo and conservativism (Barozet and Espinoza 2016; Barozet and Fierro 2011), including the general positive attitudes toward the police that characterize this group (Dammert 2013).…”
Section: Discussionmentioning
confidence: 99%